Non‐invasive and in situ investigation of layers sequence in panel paintings by portable micro‐spatially offset Raman spectroscopy. (6th July 2020) - Botteon, Alessandra; Colombo, Chiara; Realini, Marco; Castiglioni, Chiara; Piccirillo, Anna; Matousek, Pavel; Conti, Claudia
Abstract: Nowadays, the research in conservation science is focused on developing advanced portable analytical techniques able to achieve subsurface data in situ and in a non‐invasive way. Micro‐spatially offset Raman spectroscopy (micro‐SORS) is an emerging analytical technique developed to address the need of non‐invasively retrieving the molecular composition of the subsurface compounds; however, so far, micro‐SORS studies of artworks have been carried out only with benchtop Raman microscopes, precluding the non‐invasive analysis of large objects and artworks in situ. Here, for the first time, portable micro‐SORS was used for non‐invasive and in situ investigation of art objects. The potential of portable micro‐SORS is demonstrated through the reconstruction of the layer sequences in selected areas of two 16th century panel paintings, providing unequivocal information about the preparation layer spread over the panels and the pigments used in the painted layers and supplying essential information on the artist's technique. Abstract : For the first time, portable micro‐spatially offset Raman spectroscopy (micro‐SORS) was used for non‐invasive and in situ investigation of art objects. Micro‐SORS measurements permitted the reconstruction of the layer sequences in selected areas of two 16th century panel paintings, providing unequivocal information about the preparation layer spread over the panels and the pigments used in the painted layers.